2017
DOI: 10.13080/z-a.2017.104.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects and management strategies to mitigate drought stress in oilseed rape (Brassica napus L.): a review

Abstract: Oilseed rape (Brassica napus L.) is an important oilseed crop worldwide. Drought is the most detrimental environmental factor affecting the crop plants from germination up to maturity. A complete perspective of the effect of drought is crucial in understanding the influence of climate variability on rape cultivation. Water deficit stress affects morphology, physiology and development of rape crop. The aim of this article is to present an outline of the effects of drought stress on the growth, physiological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…For this reason, plant traits related to water uptake, such as seed germination capacity and root length, are of paramount importance for explaining plant adaptation and persistence in Mediterranean-type ecosystems (Valladares et al, 2004). Germination and seedling establishment are important for determination of final plants density which is highly correlated with crop yield (Raza et al, 2017). Many reports showed that seeds tolerant to drought stress during germination stage have better growth at seedling stage and also produce strong root system (Waheed, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, plant traits related to water uptake, such as seed germination capacity and root length, are of paramount importance for explaining plant adaptation and persistence in Mediterranean-type ecosystems (Valladares et al, 2004). Germination and seedling establishment are important for determination of final plants density which is highly correlated with crop yield (Raza et al, 2017). Many reports showed that seeds tolerant to drought stress during germination stage have better growth at seedling stage and also produce strong root system (Waheed, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As the first organ in plants to perceive drought stress is the root system morphology, which is not only determined by their genes but also influenced by surrounding environmental changes [12]. When plants are exposed to water-limited conditions, the root biomass and extension are inhibited [13], and lateral roots developing and root angle forming are structurally adjusted to the distribution of soil moisture [14]. In addition to such physical adaptations, roots also release certain organic compounds into the soil to improve the rhizosphere environment, which is considered as a "stress-reducing" mechanism during the long-term evolution of plants [15,16] and medium between plants and soil [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the present world, crops are suffering from drought stress, and its duration and severity are also increasing day by day due to climatic changes and thus imposing a continuous threat to food production. Drought stress hampers plant productivity through affecting normal plant growth and physiology, different biochemical processes, and yields (Raza et al 2016;Hasanuzzaman et al 2016;Cao et al 2017). Plants face oxidative stress under water deficit conditions by producing an excess amount of reactive oxygen species (ROS) which causes damage to biological molecules and cellular organelles.…”
Section: Introductionmentioning
confidence: 99%